Resilience, predictor of empathy in nursing students - Díaz-Narváez, Victor P.; Vallecampo Contreras, Andrea; Campos de Chavarría, Johanna; Estrada-Méndez, Nuvia; Sánchez de Elías, Doris Alicia; Vilca , Lindsey W.; Reyes-Reyes, Alejandro; Gamarra-Moncayo, José (Revista Cuidarte, 2025)
Highlights• The use of psychometric analysis makes it possible to prevent biases arising from non-compliance with the measurement model and should, therefore, be established as a methodological routine.• Studying resilience as a predictor of empathy requires analyzing how each dimension of resilience predicts each dimension of empathy.• This study confirms that resilience is a predictor of empathy, facilitating students’ ability to express empathically.• Although resilience and empathy develop independently, both should be introduced simultaneously in the teaching-learning processes of Nursing students.Introduction: Studies attempting to predict empathy based on resilience are characterized by incomplete theories of both constructs and focus on obtaining empirical evidence.  Objective: To verify whether resilience can predict empathy. Materials and Methods: A cross-sectional construct validity study was conducted. Salvadorean nursing students were assessed using the Jefferson Scale of Empathy-Health Professions Students (JSE-HPS) and the Engineering, Ecological and Adaptive (EEA) resilience scale. Psychometric analyses (confirmatory factor analysis, reliability, and invariance) were conducted, and prediction was assessed using structural equations. Results:  The compliance of the model of both constructs and the reliability of the data were verified. Some dimensions of resilience positively predicted the dimensions of empathy, while others predicted them negatively. Discussion: Ecological resilience and engineering resilience positively predicted all the dimensions of empathy. However, adaptive resilience negatively predicted empathy, suggesting that students may lack sufficiently developed adaptive traits to prevent declines in "compassionate care" and "standing in the patient's shoes." Therefore, their ability to connect emotionally and understand the patient's situation is hampered by a deficit of the traits that support adaptation to new situations. Conclusion: Empathy   and resilience education cannot be independent of each other. On the contrary, resilience exerts a protective effect that enables the free expression of empathy that students have developed over the course of their lives.How to cite this article: Díaz-Narváez Víctor P, Vallecampo Contreras Andrea, Campos de Chavarría Johanna, Estrada-Méndez Nuvia, Sánchez de Elías Doris Alicia, Vilca Lindsey W, Reyes-Reyes Alejandro, Gamarra-Moncayo José. Resilience, predictor of empathy in Nursing students. Revista Cuidarte. 2025;16(3):e4768. https://doi.org/10.15649/cuidarte.4768
Keywords: Resilience; Psychological; Empathy; Psychometrics; Reproducibility of Results; Students; Vocational Education